Peran Muhadharah Dalam Meningkatkan Keterampilan Komunikasi Dakwah Santri Madrasah Darul Furqon Tahfizul Qur'an PP Islahuddiny Lombok Barat NTB - Sari, Putri Novita; Budi, Rahmat Dinni Haerul (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research is backgrounded by the importance of preaching communication skills for students as prospective da’i who will play a role in spreading Islamic teachings in the community. Muhadharah as one of the traditional activities of boarding schools has strategic potential in developing students’ communication competencies, yet in-depth studies on its role in the context of modern boarding school education are still limited. Darul Furqon Tahfizul Qur'an Madrasah PP Islahuddiny West Lombok NTB organizes muhadharah activities routinely as part of the educational curriculum, so it is interesting to study how these activities contribute in improving students' preaching communication skills. The research method adopted was qualitative descriptive with data collection technique through in-depth interviews of 5 students and 2 ustadz, as well as observation of muhadharah activities. The results of the study showed that muhadharah activities made a significant contribution in improving students’ preaching communication skills through five main aspects: (1) improving public speaking ability by overcoming anxiety and developing self-confidence; (2) the development of rhetorical skills through the use of a variety of engaging delivery techniques; (3) improved mastery of preaching material through a systematic process of research and preparation; (4) mental formation and strong self-confidence through repeated experience; (5) development of adaptability to various audience characteristics. Muhadharah activities also proved relevant to the challenges of preaching in the digital age as it provided a foundation of communication skills that could be transformed to various media platforms. The study recommended the optimization of muhadharah activities by technology integration and development of more innovative variations of learning methods.